Analysis of Potential Waste-to-Energy Plant in Final Waste Disposal Sites in Indonesia Towards SDGs 2030 (A Literature Review) - Yuliana Sarasati; R. Azizah; Zia Azuro Zuhairoh; Lilis Sulistyorini; Corie Indria Prasasti; Mohd Talib Latif (Universitas Airlangga, 2021)
Introduction: Waste processing in Final Disposal Sites (FDS) in Indonesia is still dominated by open dumping. This condition causes health and environmental problems and inhibits the achievement of Sustainable Development Goals (SDGs) 2030. Waste is biomass that can be converted into electrical energy through the Waste-to-Energy Plant (WtE Plant) installation. This article aimed to illustrate the potential of WtE Plant in the FDS in Indonesia in supporting the achievement of SDGs 2030. Discussion: Most waste in the FDS are dominated by organic waste with the highwater content of 60-70% but have a calorific value almost equivalent to sub-bituminous coal. Most studies show the WtE Plant uses a thermal method (incinerator) than other technologies because it has a superior value in the technical aspects (easy operation and high generated energy around 9.86%), economy aspects (medium investment value, but high profit with moderate payback period around 6.5 years) environmental aspects (reduction of waste up to 70-80% and emissions), and lower public health impacts than those produced by open dumping and coal systems. For environmentally safe optimal results, it is necessary to reduce wastewater content, increase pollution control units, and implement an integrated monitoring system. Conclusion: The implementation of WtE Plant can accelerate to achieve the SDGs 2030, especially the 7th, 8th, 12th, and 13th goals concerning clean and affordable energy, decent jobs and economic growth, responsible consumption and production, and addressing climate change, respectively.